Circulating adiponectin and cardiovascular mortality in patients with type 2 diabetes mellitus: evidence of sexual dimorphism - Menzaghi, Claudia (BioMed Central, 2014)
BACKGROUND: The pathogenesis of cardiovascular (CV) mortality, whose rate is increased in type 2 diabetes, is poorly understood. While high serum adiponectin is associated with increased CV mortality in the general population, no data are available in type 2 diabetes. We here investigated whether this counterintuitive association was observable also in diabetic patients and whether it was sex-specific. METHODS: Three prospective cohorts were analyzed: 1) Gargano Heart Study (GHS; 359 patients, 58 events/1,934 person-years; py); 2) Health Professional Follow-up Study (HPFS; 833 men, 146 events/10,024 py); 3) Nurses’ Health Study (NHS; 902 women, 144 events/15,074 py). RESULTS: In GHS serum adiponectin predicted CV mortality in men (hazard ratio, HR, and 95% CI per standard deviation, SD, increment = 1.54, 1.19-2.01), but not women (HR = 0.98, 0.48-2.01). Circulating adiponectin predicted CV mortality in men from HPFS (HR = 1.44, 1.21-1.72), but not in women from NHS (HR = 1.08, 0.86-1.35), used as replication samples. In a pooled analysis, HRs were 1.47 (1.27-1.70) in 1,075 men and 1.07 (0.86-1.33) in 1,019 women (p for HRs heterogeneity across sexes = 0.018). CONCLUSIONS: This is the first report showing that high circulating adiponectin predicts increased CV mortality in men, but not in women with type 2 diabetes. Further studies are necessary to unravel the mechanisms through which adiponectin influences CV mortality in a sex-specific manner. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12933-014-0130-y) contains supplementary material, which is available to authorized users.